Application of Fibonacci Pattern for Network QoS (Quality of Service) Management) - gani, ahmad (Telematika, 2025)
In managing network quality of service (QoS), this study uses Fibonacci patterns to optimize delay control and bandwidth allocation. QoS is essential in contemporary network management, especially given the increasing demand for stable and effective data services. This study prioritizes data based on traffic levels using a simulated Fibonacci algorithm. Each priority is assigned a value corresponding to the Fibonacci sequence, which allows allocating resources more in line with the network load. Simulations are performed under normal and overload conditions. The results show that conventional methods, such as round-robin and weighted fair queuing, can improve QoS efficiency with Fibonacci patterns by up to 15%. This improvement mainly concentrates on controlling important data packets such as real-time communication and video streaming and reducing delay. In addition, this technique is better at adjusting to traffic changes. The results show that the Fibonacci pattern can be an innovative method for managing network QoS, especially for complex prioritization requirements. It can be a reliable tool to improve user experience with modern network services if used properly. To find out how Fibonacci patterns relate to future network technologies such as 5G and the Internet of Things, further research is needed.